Clean epitaxial MgB2 films fabricated by the exsitu annealing of chemical vapour deposition-grown B films in Mg vapour - Hanna, Mina; Wang, Shufang; Eck, Andrew David; Wilke, Rudeger H T; Chen, Ke; Soukiassian, Arsen; Lee, Che-Hui; Dai, Wenqing; Li, Qi; Redwing, Joan M; Schlom, Darrell G; Xi, X X; et al. (Superconductor science & technology, 2008)
Low residual resistivity in superconducting thin films is required for their applications in radio frequency (RF) cavities. Here we report on clean epitaxial MgB2 films fabricated by the ex situ annealing of B films, grown by chemical vapour deposition, in Mg vapour. The films show sharp superconducting transitions at about 40 K and a high residual resistivity ratio of about 10. The result indicates that a clean precursor B film and a contamination-free annealing procedure are important for a viable MgB2 film fabrication process for RF cavity applications.